EMPOWERMENT OF ORPHANS AND MOTHERS BASED ON QUR’ANIC VIEWS - Manurung, Nirwan Syafrin; Shafa, Hikmah Ismidiana; Putri, Rifania; Maulana, Imam; Kamariah, Nurul; Aziz, Muhammad Abdul; Fiqrie, Muhammad; Kurniawan, Syahrul Fauzi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
Zakat is an obligation for those who have the ability to be called Muzakki which aims to help others and for those who do not have the ability to be called Mustahik, including Fakir, Miskin, Amil, Muallaf, People who owe debts, People Who Study, and People who fight on the path of Allah Swt. Besides that, zakat can also be a tool for empowering ummah. The Muzakki, Amil and Zakat Collection Institute (UPZ) to participate in helping people alleviate poverty and social equality. Due to the Covid-19 pandemic, the number of orphans and widows has increased, this certainly affects the number of poor people, therefore zakat can be a solution. Therefore, LAZ Al-Bunyan launched a program to empower orphans and mothers as a breakthrough in an effort to provide orphan rights and contribute in accordance with the laws and verses of the Qur'an related to the empowerment of children and mothers.